Nichtvirale sexuell übertragene Infektionen: Epidemiologie, Klinik, Labordiagnostik und Therapie : Teil 2: Chlamydien und Mykoplasmen - Nenoff, Pietro; Helmbold, Peter (Der Hautarzt, 2017)
Chlamydia trachomatis is the most common pathogen of sexually transmitted bacterial infections worldwide. Every year in Germany approximately 300,000 new infections are to be expected. Chlamydia infections occur nearly exclusively in the postpubertal period. The peak age group is 15-25 years. The infection usually runs an asymptomatic course and the diagnosis is made by nucleic acid amplification techniques (NAAT) often after chlamydial screening or if complications occur. For treatment of chlamydial infections oral doxycycline 100 mg twice daily over 7 days is initially used or alternatively oral azithromycin 1.5 g as a single dose is recommended. The sexual partner should also be investigated and treated. Genital Mycoplasma infections are caused by Ureaplasma urealyticum (pathogen of urethritis and vaginitis), Ureaplasma parvum (mostly saprophytic and rarely a cause of urethritis) and Mycoplasma hominis (facultative pathogenic). Mycoplasma genitalium represents a relatively new sexually transmitted Mycoplasma species. Doxycycline is effective in Ureaplasma infections or alternatively clarithromycin and azithromycin. Doxycycline can be ineffective in Mycoplasma hominis infections and an alternative is clindamycin. Non-gonococcal and non-chlamydial urethritis due to Mycoplasma genitalium can now be diagnosed by molecular biological techniques using PCR and should be treated by azithromycin.
Online publiziert: 15. Dezember 2016
Gesehen am 03.05.2018